2019
DOI: 10.1039/c8sc05006f
|View full text |Cite
|
Sign up to set email alerts
|

A robust ALD-protected silicon-based hybrid photoelectrode for hydrogen evolution under aqueous conditions

Abstract: Hybrid systems combining molecular catalysts with inorganic materials is a promising solution towards cheap yet efficient and stable photoelectrochemical hydrogen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Preparation of Zr(NDI) thin films. ALD-deposited TiO 2 has been used as an interface to immobilize molecular catalysts at semiconductors [22][23][24]31 , and in our construct, provides a metal oxide surface for anchoring the carboxylate-functionalized NDI linker. TiO 2 was deposited by ALD onto freshly etched semiconductor (SC, where SC is Si or GaP) wafers using 100 alternating TiCl 4 :H 2 O cycles at 200°C, which results in TiO 2 @SC samples amenable to the attachment of carboxylate groups 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of Zr(NDI) thin films. ALD-deposited TiO 2 has been used as an interface to immobilize molecular catalysts at semiconductors [22][23][24]31 , and in our construct, provides a metal oxide surface for anchoring the carboxylate-functionalized NDI linker. TiO 2 was deposited by ALD onto freshly etched semiconductor (SC, where SC is Si or GaP) wafers using 100 alternating TiCl 4 :H 2 O cycles at 200°C, which results in TiO 2 @SC samples amenable to the attachment of carboxylate groups 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Formation of a p-n junction at p-GaP using an ALD-deposited layer of n-Nb 2 O 5 and a Pt catalyst resulted in a record photovoltage of 710 mV, an improvement of 360 mV compared to a GaP photocathode with Pt only and no metal oxide layer 9 . Molecular functionalization of semiconductors can also lower barriers for photoelectrochemical reactions 14,[17][18][19][20][21][22][23][24][25] . In the context of metal-organic hybrid constructs, Downes and Marinescu 26 demonstrated photoelectrochemical H 2 evolution in H 2 SO 4 solution (pH 1.3) by a cobalt dithiolene polymer composing a metal-organic surface (MOS) dropcast onto p-type Si electrodes.…”
mentioning
confidence: 99%
“…Additional evidence that the photocurrent is under diffusional control is found through modeling the current under finite diffusion conditions. P-type Si and GaP have previously been used as substrates for hydrogen evolution and carbon dioxide reduction, [20][21][22][23][46][47][48][49][50] and these findings indicate that the advantages of MOFs, such as their high surface area and porosity combined with their ability to house and stabilize molecular catalysts, may be integrated with these SCs for MOF-based photoelectrosynthetic applications. We have shown that the construct can be operated in aqueous conditions, a promising feature in the context of light-driven hydrogen evolution.…”
Section: Resultsmentioning
confidence: 97%
“…9 Molecular functionalization of semiconductors can also lower barriers for photoelectrochemical catalysis. 14,[17][18][19][20][21][22][23][24][25] In the context of metal-organic hybrid constructs, Downes and Marinescu demonstrated photoelectrochemical H2 evolution in H2SO4 solution (pH 1.3) by a cobalt dithiolene polymer composing a metal-organic surface (MOS) dropcast onto p-type Si electrodes. 26 In this study, the electrochemical potential required to achieve equivalent rates of H2 evolution was 550 mV less under illumination than that of the MOS at Scheme 1.…”
Section: Couplesmentioning
confidence: 99%
See 1 more Smart Citation